Os mundos rural e urbano: relações e interações a partir do cotidiano da comunidade de São João no Vale do Ribeira - PR - Alves, Ana Paula Aparecida Ferreira (2011)
The purpose of this dissertation is to understand the relationships and interactions among the rural and urban worlds, considering the daily life in São João, a rural community maroon. The isolation and the constraints arising from the geographical condition of this maroon community, located in the Vale do Ribeira – PR, force residents to seek resources and better infrastructure in other locations. In consequence, they develop different strategies and dynamics of dislocations as an alternative to face this scenario. This research seeks to understand how these relationships are given from the experience lived and what that entails in day-to-day of community.Through community studies, it was possible to reconcile theory and method. Through the community studies, it was possible to combine the theory with the method, as the micro-scale perspective make possible to appreciate each researched individual’ view. The research results have been achieved by observing their daily life and accompanying their daily movements. Interviews and a genealogy construction together with the residents were also essential. Some factors, such as the creation of the Park of Lauráceas and the spatial compression of farmers from the 1970s on, helped to increase the isolation and the rural exodus in the community. The lack of basic resources also motivates them to search in the urban world what they do not find in their own rural world. The current relations made between these two worlds have shown an integration between the two and changing life in the community.